Duplicated middle cerebral artery arising from the origin of the hyperplastic anterior choroidal artery that mimicked aneurysm on routine MR angiography. Issue 2 (April 2016) - Uchino, Akira; Ito, Sayaka; Kurita, Hiroki; Tanaka, Masahiko
We report a case of duplicated right middle cerebral artery that arose from the origin of the right hyperplastic anterior choroidal artery diagnosed by magnetic resonance angiography. To our knowledge, this is the first case of such a variation reported with magnetic resonance angiographic images. The internal carotid artery–hyperplastic anterior choroidal artery-duplicated middle cerebral artery junction was dilated and mimicking aneurysm. Partial maximum intensity projection images and volume-rendering images showed that it was not a saccular aneurysm but an infundibular dilatation. Careful observation of magnetic resonance angiographic images including its source images is important for detecting rare arterial variations. To identify an anomalous artery on magnetic resonance angiography, creation of partial maximum intensity projection images and volume-rendering images is valuable.